National ecosystem restoration pledges are mismatched with social-ecological enabling conditions - Felipe Benra; Maria Brück; Emily Sigman; Manuel Pacheco-Romero; Girma Shumi; David J. Abson; Marina Frietsch; Joern Fischer (Communications Earth & Environment)
Abstract Ecosystem restoration is widely recognized as a key strategy to address social-ecological challenges. National governments have pledged to restore millions of hectares of land. However, the ability to accomplish these pledges remains opaque, because restoration efforts are influenced by complex social-ecological factors. We provide a global analysis of national-level enabling and hindering conditions and their relation to restoration pledges undertaken by different nations. We developed an archetype characterization of within-country conditions using biophysical, socio-economic and governance indicators. Additionally, we investigated between-country conditions by examining flows of embodied land. Our analysis suggests that the countries with the most ambitious restoration pledges also tend to have the weakest enabling conditions (and vice versa). These results highlight the need to account for social, economic and governance factors alongside biophysical factors when considering where restoration ought to take place.